The Origin and Significance of the Korean Boy Scout Movement during the Japanese Occupation. Issue 3 (8th June 2022) - Lee, Karam; Ok, Gwang
Abstract: In the early twentieth century, the Boy Scout Movement gained prominence as a worldwide boys' movement. The movement, which was created during the Edwardian era to defend and maintain the British Empire, spread internationally in accordance with each nation's disparate political and social needs. From this perspective, the Joseon (Korea's national name during the Japanese colonial period) Boy Scout Movement emerged rapidly as a base for practical anti-imperialist resistance. Within the colonial space of Japanese rule, the boys of Joseon were able to foster physical fitness and masculinity through the Boy Scout Movement, thereby fostering a national consciousness and thus growing as autonomous agents capable of resisting the Japanese Empire. The educational activities of the Boy Scouts functioned as a channel for the proliferation and development of modern physical education and sports culture in Korea.